Bridge management system : review on current system and a case study - Noor Hidayah , Muhamad Jamil (2012)
Over the centuries, bridge agencies faced a common problem which is deterioration of bridges. However, even after acknowledge of the problem, the agencies still unable to settle it down because of unorganized of the obtained data. Thus, the bridge agencies started to adopt an approach in managing their bridge which is called bridge management. The bridge management system are then develop as a tool to operate and analyse the bridge management activities. Ussually, each country have their own bridge management system. For examples, Malaysia (JKR BMS), Denmark (DANBRO) and U.S.A (PONTIS). The modules installed in these systems made the systems differ with one another. Each modules offer different functions for the system and made the systems unique. The quality of the bridge management systems depends on the installed modules and the systematic and effective bridge management depends on the systems. The systematic and effective bridge management system is able to manage bridge activities efficiently.